1993
DOI: 10.1002/jsfa.2740610411
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of the starchy flour extracted from cassava on fermentation with a mixed culture inoculum

Abstract: Abstract:The functional properties of the starchy flour extracted from six varieties of cassava subjected to fermentation by a mixed culture inoculum comprised of lactobacilli, streptococci, corynebacteria and yeast cells are examined. Apparent reduction in total and soluble amylose contents is observed. Differential scanning calorimetry of the samples indicated that the enthalpy of gelatinisation was reduced, while the gelatinisation temperature was enhanced. A marked reduction in Brabender viscosity values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 8 publications
(7 reference statements)
4
15
0
1
Order By: Relevance
“…During the cooling step, a viscosity rise was observed, but with weak gel characteristics (Jane et al, 1992). A different pasting profile has been reported in other taro starch studies (Lu et al, 2008;Moorthy, Mathew, & Padmaja, 1993;Pérez et al, 2005;Tattiyakul et al, 2007). The pasting profile of high-protein commercial amaranth starch, with the ability to produce "popcorn" balls formed of granules cemented together in spherical aggregates, showed a higher peak viscosity than amaranth starch isolated in the laboratory.…”
Section: Pasting Profilementioning
confidence: 74%
“…During the cooling step, a viscosity rise was observed, but with weak gel characteristics (Jane et al, 1992). A different pasting profile has been reported in other taro starch studies (Lu et al, 2008;Moorthy, Mathew, & Padmaja, 1993;Pérez et al, 2005;Tattiyakul et al, 2007). The pasting profile of high-protein commercial amaranth starch, with the ability to produce "popcorn" balls formed of granules cemented together in spherical aggregates, showed a higher peak viscosity than amaranth starch isolated in the laboratory.…”
Section: Pasting Profilementioning
confidence: 74%
“…8 DSC studies showed that the gelatinisation temperature was significantly higher for the starch from fermented sweet potato tubers for most of the cultivars. Among the six cultivars studied, a decrease in the enthalpy of gelatinisation was observed for the fermented starches from three cultivars, and there was no significant change in H for CV and SR.…”
Section: Discussionmentioning
confidence: 99%
“…7 When cassava is fermented before extraction, the starch undergoes minor changes in its properties, but the main structural features are unaffected. 8 Unlike cassava, sweet potato starch takes a longer time to settle and the yield is poor on extraction. It is surmised that suitable lactic acid fermentation with a select group of organisms could lower the pH of the steep liquor so as to prevent oxidation of phenolic compounds in sweet potatoes, which causes discolouration of the starch.…”
Section: Introductionmentioning
confidence: 99%
“…• C. 40 This leads to an expansion of cell size and volume, cell separation and cell wall distension, depending on the starch content. 41,42 In the present study the starch content of the tubers varied from 74.94 to 82.26% db.…”
Section: Textural Degradation During Cookingmentioning
confidence: 99%